PELATIHAN PEMANFAATAN BARANG BEKAS SEBAGAI MEDIA PEMBELAJARAN - Nabila Mega Oktapiani; Yudi Budianti; Rima Rikmasari (Universitas Islam 45 Bekasi, 2023)
Garbage is material that is disposed of by humans and is not used. Garbage is a very big problem, besides having a sale value, trash or used goods can be used to make learning media that are very useful for the learning process. Learning media is one of the tools used by teachers and functions to stimulate the mind, attention, and motivation to learn in students. The implementation method using community education and training methods aims to increase teacher creativity and can reduce waste pollution in Lennggajaya Village. The results of the service prove that learning media can help students' thinking processes become faster and easier to understand, arouse student motivation and teaching methods will be more varied. Based on the results of this evaluation, it can have an impact on reducing the accumulation of waste in Leggahjaya Village. By utilizing used goods in the surrounding environment, it can help in terms of waste management and using used goods as learning media in elementary schools, so it will directly save costs in making media in schools.